Out-of-hospital cardiac arrest: always coronary angiography?. (2nd November 2017) - Rognoni, Andrea; Cavallino, Chiara; Mennuni, Marco Giovanni; Barbieri, Lucia; Rosso, Roberta; Rametta, Francesco; Nardi, Federico; Lupi, Alessandro; Bongo, Angelo Sante
ABSTRACT: Introduction : Out-of-hospital cardiac arrest (OHCA) remains one of the principle challenges in the setting of critical care medicine and emergency cardiology. Areas covered : Long-term survival rates even after successful resuscitation are variable but increasing in the recent years; due to the improvement of base and advanced cardiac life support techniques an increasing number of resuscitated patients are admitted to the hospital. Recent data suggested that patients surviving to hospital discharge after OHCA presented long-term outcome similar to patients with ST-elevation myocardial infarction. However, limited and incompletely clear data are available in the literature about the selection and risk stratification of patients to be subjected to coronary angiography, particularly in patients who have unfavorable clinical features in whom procedures may be futile and may affect public reporting of morality. Recently the ESC and AHA addressed appropriate treatments for ST-elevation myocardial infarction (STEMI) patients with out-of-hospital cardiac arrest. Expert commentary : Immediate coronary intervention in the setting of OHCA appears to be associated with better survival to discharge; the documentation of an occluded coronary artery in medium 25% of patients without signs of STEMI at ECG helps to explain why early angiography can improve outcomes. In the treatment of OHCA we can find some ethical issues; for example a combination of comorbidities with advanced age and prolonged ischemia indicated by severe lactic acidosis may signify a high enough chance of multiorgan failure or anoxic brain injury and where the benefit of coronary reperfusion therapy appears minimal.